London bridges - Patterson, James (New York : Warner Vision Books, 2005)
When the world's largest cities are seized by terrorists who threaten to set off deadly bombs unless their demands are met, Alex Cross heads a joint investigation by the FBI, CIA, and Interpol to outmaneuver two vicious criminals known as the Weasel and the Wolf.
Keywords: Police -- Washington (D.C.) -- Fiction; Psychological fiction